MĘDREK SPRZEDAJE NIEWOLNIKA, CZYLI WADY TOWARU W ANTYCZNYM DOWCIPIE - Tarwacka, Anna (Zeszyty Prawnicze, 2016)
A LEARNED FOOL SELLS A SLAVE. DEFECTIVE SALES GOODS IN AN ANCIENT JOKE Summary The aim of the article is to analyse and explain the joke in Philogelos 18 by bringing out its legal connotations. The joke is about a learned fool being informed by the buyer that the slave he has sold him has died. The fool replies that the slave had never done such a thing before. The legal background is the seller’s liability for physical defects in the sales goods, which was regulated by the Aedilician edict De mancipiis emundis vendundis as regards slaves. While the buyer seems to be referring to an illness as the presumable cause of the slave’s death, the seller’s answer would only make sense if it applied to another “defect” – the slave running away. Both situations were usually covered in the seller’s guarantee for the quality of the product. If the slave had escaped, the assertion that he had never done that before would have been perfectly logical, because – if proven – it would have exonerated the seller from liability.